The Role of Operational Efficiency, Liquidity, Leverage, and Company Growth on Company Value at IDX - Nurfa Rini Husvifa; Suhardi Suhardi; Jufri Sani Akbar (Electronic Journal of Education, Social Economics and Technology, 2025)
This study aims to analyze the influence of Return on Assets, Current Ratio, Debt to Equity Ratio, and company growth on the company's value variables using panel data regression.  The sample in this study is pharmaceutical sector companies listed on the Indonesia Stock Exchange from 2019-2023. The results of the study show that ROA and CR have a positive and significant influence on the company's value variables. The DER and GROWTH variables have no significant influence on the company's value variables. Based on the results of the research, the next research can consider the addition of other variables that have the potential to have more influence on dependent variables, such as capital structure, operational efficiency, or external factors such as macroeconomic conditions. To obtain more accurate results, future research may try to use other regression methods, such as the Fixed Effect Model (FEM) or the Generalized Method of Moments (GMM), which may be more appropriate in capturing relationships between variables. This study only used a limited sample of certain companies. Subsequent studies may also expand the scope by examining different industry sectors or comparing results between large and small companies to understand broader dynamics, including considering using data over a longer period, as well as considering the effects of market dynamics and changes in economic policies.